INTERNAL AUDITOR CHARACTERISTICS AND FINANCIAL REPORTING QUALITY: EVIDENCE FROM BANGLADESH - Khan, Md Gulam Sharoar Hossain (Indian Journal of Finance and Banking, 2023)
This study aims to examine the relationship between internal auditor characteristics and financial reporting quality in the context of the banking sector in Bangladesh. To achieve this objective, this study used a quantitative research methodology by using a questionnaire survey. Data were collected (495 respondents from 45 banks) from the internal auditors of banking companies in Bangladesh which cover 78% of the population. This study uses five important characteristics of internal auditors as exogenous variables such as auditors’ independence, auditor proficiency, professional qualification, auditors’ experiences, and the leadership style of the chief audit executive. SmartPls-4 is used as statistical software to determine the relationship between exogenous and endogenous constructs. Findings indicate that professional qualification has the highest positive significant impact on financial reporting quality. Results also revealed that other characteristics like au auditors’ independence, auditor proficiency, and auditors’ experiences has also positive significant effects on financial reporting quality. However, the leadership style of the chief audit executive has no positive significant impact on financial reporting quality. The findings of this study encourage the level of understanding of the internal auditors, regulators, top management, policy maker of the organization, investors, and other stakeholders regarding the quality of financial reporting of banking sectors in the perspective of an emerging economy. JEL Classification Codes: M40, M41, M42, H83, F65.